Two Types of Verb Reduplications in Mandarin Chinese - Xie Zhu (Sciendo, 2020)
This paper analyzes verb reduplication in Mandarin Chinese under a lexicalist framework. By adopting the Lexicalist Hypothesis proposed by Chomsky (1970), a distinction has been made between syntactic and morphological verb reduplications by means of five tests: productivity, le insertion, categorial stability, transitivity, and input/output constraints. It is found that the AA and ABAB patterns of verb reduplication have relatively high productivity and regular syntactic behaviors, whereas the AABB pattern of verb reduplication shows extremely low productivity and syntactic idiosyncrasy. Given these observations, this paper proposes that the AA and ABAB patterns should be syntactic verb reduplications derived at the syntactic level, whereas the AABB pattern should be morphological verb reduplication formed in the lexicon. The two types of verb reduplications have different generative mechanisms.